Integrative Approaches to Sustainable Development at University Level: Making the Links - Leal Filho, W (Springer, 2015)
This book documents and compares the experiences of a wide range of universities across the five continents with regard to sustainable development, making it of special interest to sustainability researchers and practitioners. By showcasing how integrative approaches to sustainable development at the university level can be successfully employed to bridge the gaps between disciplines, the book provides a timely contribution to the literature on sustainability and offers a valuable resource for all those interested in sustainability in a higher education context.